IDENTIFIKASI KUALITAS DAN BOBOT MASA SIMPAN BEBERAPA JENIS BUAH SALAK BALI (Salacca Zalacca Var. Amboinensis) - Ni Kadek Emawati; I Dewa Nyoman Raka; I Made Suryana; Farida Hanum; Putu Eka Pasmidi Ariati (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2022)
Bali salak fruit is one of the preferred fruit plants and has good prospects for cultivation. and the production of salak fruit is very large. This study, entitled "Identification of the quality and shelf-life of several types of salak Bali (Salacca zalacca var. Amboenensis)" was carried out at the center of salak development in Sibetan Village, Karangasem Regency, Bali. This study aimed to identify the quality and shelf life of several types of Balinese salak in Sibetan Karangasem. And get the type of salak bali which has the best quality and weight of the shelf life of salak fruit. This study used randomized block design (RAK) using 8 treatments which were repeated 4 times so as to get 32 treatments, the results of the identification of the quality and weight of the shelf life of salak fruit gave a very significant effect on the number of bunches of fruit, fruit weight, shelf life weight, and had an effect on significantly on the weight of the bunch, the thickness of the flesh and the level of acidity in the medium, the low level of TPT (total dissolved solids), and the high level of vitamin C. And the salak fruit that has the best quality and shelf-life weight is sugar salak with a mass of 48.75 g, and the quality of salak acid content of granulated sugar with a value of 18.3 pH, TPT (total dissolved solids) with a value of 0.34, and vitamin C content with a value of 199.61 mg